(untitled) (Research, Society and Development, 2023)
Objective: This study aimed to assess the challenges and limitations that nursing care faces during the sedation process. Methodology: This is an integrative literature review of a descriptive nature, with a qualitative approach. To carry out this study, the following databases were used: Regional Portal of the Virtual Health Library (VHL), Scientific Electronic Library Online (SciELO) and the National Library of Medicine (PubMed). Inclusion criteria were used: articles published between 2012 and 2022, which addressed the topic clearly and objectively, available in Portuguese, English or Spanish. The non-inclusion criteria were: incomplete articles, repeated in the databases, that deviated from the proposed theme or were not in the indicated period and in the proposed language. Results and Discussion: The main limitation of nursing care in the ICU is the lack of autonomy in the sedation process, so it is not up to the nursing team to intervene or prescribe doses or medications, it is the role of the nurse to administer the medications, check the dosage and drug before applying and, monitoring the responses of the sedated patient. The two major challenges that the nursing team faces are the lack of sedation protocols and the lack of adequate training for nursing teams. Conclusion: The nursing team plays a key role in the sedation process, as it monitors and cares for the sedated patient until he or she recovers.